Development and application of the FISHTRAC real-time remote monitoring tool for digital twinning of river basins in southern Africa - Kaiser-Reichel, A.; Burnett, M.; Dickens, Christopher; McNiel, T.; Retief, H.; Süßle, V.; Garcia Andarcia, Mariangel; O’Brien, G. C. (International Water Management Institute (IWMI). CGIAR Initiative on Digital Innovation, 2024)
The natural world consists of various complex physical, biological and social systems that are connected and interact with each other. New technological developments are improving the ability of the managers of natural resources, to understand and contribute to the way we are developing using and sometime abusing our resources. Through the Digital Twin for management of water resources in the Limpopo River Basin we have an opportunity to integrate available sustainable environmental flows and water resource management technology into an integrated system, that will allow stakeholders of the Limpopo River and surrounding regions to understand, monitor and manage these resources for current and future generations.